Evidence Based Treatment Strategies For “Text Neck Syndrome ”: A Review - Shinde, Sandeep; Bhende, Radha (International Journal of Occupational Safety and Health, 2023)
Introduction: Text neck syndrome is an overuse condition or repetitive stress injury in which the cervical spine is flexed forward or down for extensive stretch while gazing at the smartphone or other electronic device. Individual with this Syndrome usually present with neck pain, restricted cervical range of motion, reduced muscle strength and endurance, altered cervical joint position error along with postural alterations like forward head posture and rounded shoulders as well. Methods: We performed a systematic review on the Text Neck Syndrome and discussed the evidence-based studies. For the purpose of the review, an electronic search for relevant articles using PUBMED, MEDLINE, Pedro, Research Gate, Google Scholar and CINHAL databases up to March 2022 was done wherein MeSH search terms and free words were used. In addition to the electronic search, articles were searched manually for relevant studies. Articles were selected based on authors expertise, self- knowledge and reflective practice. Results:The current study included 17 articles that fulfilled the inclusion criteria suggesting that Text Neck Syndrome is an upcoming concern and requires attention .The above reviewed studies provided evidence that physiotherapy as a mode of treatment is definitely effective in treating the Text Neck Syndrome. Conclusion: This review spoke about the text neck syndrome and its rising consequences and also about the treatment approaches available in treating and minimizing the symptoms of this syndrome. Further research is required over what more preventive strategies can be adopted in case of the Text neck syndrome.